Structural, morphological and electrochemical investigation of LiNi0.6Co0.2Mn0.2O2 cathode material synthesized in different sintering conditions. Issue 9 (November 2015) - Xia, Yun-Fei; Nie, Min; Wang, Zhen-Bo; Yu, Fu-Da; Zhang, Yin; Zheng, Li-Li; Wu, Jin; Ke, Ke
Abstract: Layered structure LiNi0.6 Co0.2 Mn0.2 O2 cathode material was synthesized via a two-step solid state reaction with industrial Ni0.6 Co0.2 Mn0.2 (OH)2 and Li2 CO3 in this paper. The samples prepared at different sintering temperatures (750–850 °C) and sintering times (10–18 h) were analyzed by physical and electrochemical methods to gain the optimal sintering condition, and an additional XRD Rietveld refinement was taken to get more reliable structural parameters. The results demonstrated that the higher temperature leads to larger primary particle size and severer agglomeration, while duration factor may affect the electrochemical performance rather than the structure and morphology of the materials. The optimized NCM622 material has an initial discharge capacity of 156.3 mA h g −1 at 1 C, whose capacity retention even reached 102.9% after 100 cycles. In addition, the three dispersed peaks ( P 1, P 2, P 3) in particle distribution analysis and R SEI, R e, R ct in electrochemical impedance spectroscopy have been separated and discussed in detail.